Improvement of exercise capacity after early phase II cardiac rehabilitation in patients who undergo rheumatic mitral valve surgery - Ade Meidian Ambari; Budhi Setianto; Anwar Santoso; Basuni Radi; Bambang Dwiputra; Eliana Susilowati; Fadila Tulrahmi; Pieter A Doevendans; Maarten Jan Cramer (The Indonesian Heart Association, 2020)
Background: Rheumatic heart disease still become a major concern in developing countries. Recent studies showed the benefits of early phase II cardiac rehabilitation (CR) on improving the exercise capacity but the evidence in patients after rheumatic mitral valve surgery due to rheumatic heart disease is limited. This study aims to investigate the effects of early phase II CR program on increasing exercise capacity in the rheumatic mitral valve surgery patients. Methods: This is a cohort retrospective study. A review of medical records identified 254 patients who underwent early phase II CR after rheumatic mitral valve surgery between July 2009 – June 2019. Effects of CR was assessed by 6 Minutes Walking Distance (6MWD) pre and post early phase II CR and peak oxygen uptake (VO2 peak) calculated by Cahallin formula. In this study, we observed and analyzed the increasing of 6MWD and VO2 peak. Results: Our findings showed that 6MWD and VO2 peak increased significantly in these patients after early phase II CR program (p = 0.001). Mean of 6MWD increased from 316.3 ± 71.7 meters to 378.6 ± 60.3 meters and VO2 peak increased from 7.7 ±2.4 mL/kg/min to 8.9 ± 2.2 mL/kg/min. The mean difference of 6MWD was 62.3 meters and VO2 peak was 1.2 mL/kg/min. There was a strong correlation between VO2 peak and 6MWD (r = 71%; R2 = 51%; p = 0.001). Conclusion: Early phase II CR in patients with Rheumatic Mitral Stenosis after mitral valve surgery improved the exercise capacity. Based on 6MWD, we can predict the value of VO2 peak patients with rheumatic mitral stenosis surgery patients. Keywords: Cardiac rehabilitation, rheumatic mitral stenosis, 6MWD, VO2 peak